A transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202311596390.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-27
AI Technical Summary
[0004]针对现有技术中存在的问题,本发明提供一种过渡金属掺杂的壳聚糖基碳气凝胶双功能电催化剂及其制备方法和应用,从而解决现有技术中碳材料比表面积较差导致催化活性中心较少,同时过渡金属催化剂倾向于直接在碳材料表面生长或螯合,结合力较差,导致材料的使用寿命较差的技术问题
[0020] This invention discloses a method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst. Chitosan is used as the main raw material. The molecular structure of chitosan contains a large number of amino groups that can chelate and coordinate with transition metals, which can effectively achieve the chelation and anchoring of nickel ions. At the same time, nanocellulose suspension is added to effectively provide structural support for the carbon aerogel, so that the material can effectively maintain a good three-dimensional pore structure during the carbonization process, resulting in a good specific surface area. Here, nickel ions are chelated inside the carbon aerogel. Then, the nickel-doped carbon aerogel was placed in a phthalocyanine iron solution and stirred to obtain a nickel-doped carbon aerogel adsorbed with phthalocyanine iron. The nickel-doped carbon aerogel adsorbed with phthalocyanine iron was then subjected to a secondary carbonization treatment under a mixed atmosphere of Ar and H2 to prepare the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst. During this process, the phthalocyanine iron compound was adsorbed onto the surface of the carbon material through π-π conjugation, effectively avoiding interaction with the nickel inside the carbon aerogel and effectively maintaining the activity of the bifunctional electrocatalyst. In the preparation process, the nickel-doped carbon aerogel adsorbed with phthalocyanine iron was carbonized under a mixed atmosphere of Ar and H2. On the one hand, the reducing atmosphere allowed iron atoms to be fixed on the carbon aerogel; on the other hand, the reducing atmosphere etched the surface of the carbon aerogel, effectively increasing the active sites on the carbon aerogel surface, thereby improving the catalytic performance of the material. This invention utilizes biomass materials as the carbon-based material, constructing a 3D porous carbon aerogel through freeze-drying and pyrolysis. The incorporation of transition metals is optimized by leveraging the chelating effect of transition metals and the π-π conjugation between the macrocyclic structure of phthalocyanine compounds and carbon materials, thereby improving the catalytic performance of the carbon aerogel. This invention also crosslinks chitosan with rigid macromolecular chain nanocellulose to form a porous aerogel. The incorporation of transition metals is optimized by utilizing the chelating effect of the special functional groups of biomass materials with metal ions and the π-π conjugation between phthalocyanine compounds and carbon materials, anchoring the transition metals onto the biomass carbon material to form a bifunctional electrocatalyst doped with two transition metals. This method is simple to prepare, the process is controllable, and it effectively improves the catalytic performance of transition metals, providing a new approach to electrocatalysts in the field of zinc-air batteries.
Smart Images

Figure CN117438598B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalysis and energy storage material development technology, and relates to a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, its preparation method and application. Background Technology
[0002] Currently, human development is increasingly dependent on energy, fossil fuels are being rapidly consumed, and the depletion of limited non-renewable energy sources, along with corresponding increases in environmental pollution, are escalating dramatically. The pressure of energy depletion and environmental pollution compels us to continuously search for new energy sources and new energy storage and conversion devices. In recent years, zinc-air batteries have become a research hotspot due to their high energy density and pollution-free nature. However, the slow kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) severely limit their applications. Currently, ruthenium (Ru) and iridium (Ir) oxides are considered the most effective OER electrocatalysts, while platinum (Pt)-based materials are considered to have relatively good ORR performance. However, these catalysts are all noble metal-based catalysts, which suffer from drawbacks such as high cost and resource scarcity. Therefore, developing inexpensive, highly active non-noble metal materials as electrocatalysts to replace noble metal electrocatalysts is a key research direction in the field of electrochemistry. Transition metals (Fe, Co, and Ni) and their derivatives have been shown to be active centers for OER / ORR, and the ORR / OER performance of non-noble metal-based catalysts can be modulated using various methods such as electronic structure modulation, defect structure construction, and integration of appropriate supports. However, their relatively weak catalytic performance and conductivity have limited the widespread application of transition metals as catalysts in air batteries.
[0003] Carbon materials have been widely used in catalyst supports, electrocatalysis, and supercapacitors due to their high electrical conductivity, acid and alkali resistance, and wide availability. However, most carbon materials currently have limited specific surface area, resulting in fewer active sites and thus fewer catalytic active centers. Furthermore, transition metal catalysts tend to grow directly on or chelate onto the surface of carbon materials, leading to poor bonding and shortening the material's lifespan. i Their fate was rather unfortunate. Summary of the Invention
[0004] To address the problems existing in the prior art, this invention provides a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, its preparation method, and its application. This solves the technical problems in the prior art where the poor specific surface area of carbon materials leads to fewer catalytic active centers, and the transition metal catalysts tend to grow or chelate directly on the surface of carbon materials, resulting in poor binding force and thus poor material lifespan.
[0005] This invention is achieved through the following technical solution:
[0006] A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst includes the following steps:
[0007] S1: Add soluble nickel salt to chitosan solution, stir to completely dissolve soluble nickel salt, then add nanocellulose suspension, and continue stirring to mix evenly;
[0008] S2: The mixture obtained in step S1 is freeze-dried to obtain nickel-doped chitosan aerogel, and the nickel-doped chitosan aerogel is carbonized once to obtain nickel-doped carbon aerogel.
[0009] S3: The nickel-doped carbon aerogel is placed in a phthalocyanine iron solution and stirred to obtain a nickel-doped carbon aerogel adsorbed with phthalocyanine iron. Then, the nickel-doped carbon aerogel adsorbed with phthalocyanine iron is placed in a mixed atmosphere of Ar and H2 for secondary carbonization treatment to obtain the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst.
[0010] Preferably, in step S1, the mass ratio of chitosan to nickel chloride is (0.5-2)g:(0.1-0.5)g.
[0011] Preferably, in step S1, the soluble nickel salt is at least one of nickel chloride, nickel nitrate, and nickel sulfate.
[0012] Preferably, the chitosan solution is prepared by adding chitosan to an acidic solution and stirring until the chitosan is completely dissolved. The acidic solution is any one of acetic acid, hydrochloric acid, nitric acid, and sulfuric acid.
[0013] Preferably, in step S2, the temperature of the carbonization process is 700–900°C and the time is 2–5 hours.
[0014] Preferably, in step S3, the treatment time of placing the nickel-doped carbon aerogel in the phthalocyanine iron solution is 1 to 5 hours.
[0015] Preferably, in step S3, the temperature of the secondary carbonization treatment is 500–800°C, and the time is 2–5 hours.
[0016] Preferably, the content of phthalocyanine iron in the phthalocyanine iron solution is (1-100) mg / 50 mL.
[0017] A transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, prepared by the method described in claim 1.
[0018] The above-mentioned application of a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst in the field of zinc-air batteries.
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] This invention discloses a method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst. Chitosan is used as the main raw material. The molecular structure of chitosan contains a large number of amino groups that can chelate and coordinate with transition metals, which can effectively achieve the chelation and anchoring of nickel ions. At the same time, nanocellulose suspension is added to effectively provide structural support for the carbon aerogel, so that the material can effectively maintain a good three-dimensional pore structure during the carbonization process, resulting in a good specific surface area. Here, nickel ions are chelated inside the carbon aerogel. Then, the nickel-doped carbon aerogel was placed in a phthalocyanine iron solution and stirred to obtain a nickel-doped carbon aerogel adsorbed with phthalocyanine iron. The nickel-doped carbon aerogel adsorbed with phthalocyanine iron was then subjected to a secondary carbonization treatment under a mixed atmosphere of Ar and H2 to prepare the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst. During this process, the phthalocyanine iron compound was adsorbed onto the surface of the carbon material through π-π conjugation, effectively avoiding interaction with the nickel inside the carbon aerogel and effectively maintaining the activity of the bifunctional electrocatalyst. In the preparation process, the nickel-doped carbon aerogel adsorbed with phthalocyanine iron was carbonized under a mixed atmosphere of Ar and H2. On the one hand, the reducing atmosphere allowed iron atoms to be fixed on the carbon aerogel; on the other hand, the reducing atmosphere etched the surface of the carbon aerogel, effectively increasing the active sites on the carbon aerogel surface, thereby improving the catalytic performance of the material. This invention utilizes biomass materials as the carbon-based material, constructing a 3D porous carbon aerogel through freeze-drying and pyrolysis. The incorporation of transition metals is optimized by leveraging the chelating effect of transition metals and the π-π conjugation between the macrocyclic structure of phthalocyanine compounds and carbon materials, thereby improving the catalytic performance of the carbon aerogel. This invention also crosslinks chitosan with rigid macromolecular chain nanocellulose to form a porous aerogel. The incorporation of transition metals is optimized by utilizing the chelating effect of the special functional groups of biomass materials with metal ions and the π-π conjugation between phthalocyanine compounds and carbon materials, anchoring the transition metals onto the biomass carbon material to form a bifunctional electrocatalyst doped with two transition metals. This method is simple to prepare, the process is controllable, and it effectively improves the catalytic performance of transition metals, providing a new approach to electrocatalysts in the field of zinc-air batteries.
[0021] Furthermore, in step S1, the mass ratio of chitosan to nickel chloride is (0.5-2)g:(0.1-0.5)g, which allows an appropriate amount of nickel ions to chelate with the amino groups on the chitosan.
[0022] Furthermore, in step S1, the soluble nickel salt is at least one of nickel chloride, nickel nitrate, and nickel sulfate, which allows nickel ions to rapidly chelate with the amino groups on chitosan.
[0023] Furthermore, the chitosan solution is prepared by adding chitosan to an acidic solution and stirring until the chitosan is completely dissolved. The acidic solution is any one of acetic acid, hydrochloric acid, nitric acid, and sulfuric acid, which allows the water-insoluble chitosan to gain protons and form positively charged cationic groups, thereby slowly dissolving in water.
[0024] Furthermore, in step S2, the temperature of the first carbonization treatment is 700-900℃ and the time is 2-5h, which can make the freeze-dried aerogel completely graphitized.
[0025] Furthermore, in step S3, the nickel-doped carbon aerogel is placed in a phthalocyanine iron solution for 1 to 5 hours, which allows the phthalocyanine iron to fully combine with the carbonized carbon aerogel.
[0026] Furthermore, in step S3, the temperature of the secondary carbonization treatment is 500-800℃ and the time is 2-5h, which allows phthalocyanine iron to gradually carbonize and fix on the surface of carbon aerogel.
[0027] Furthermore, the phthalocyanine iron solution contains (1-100) mg / 50 mL of phthalocyanine iron, which allows an appropriate amount of phthalocyanine iron to form a π-π conjugation effect with the carbon aerogel, effectively improving the binding force of iron on the carbon aerogel surface. Attached Figure Description
[0028] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 This is a schematic flowchart of a method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to the present invention.
[0030] Figure 2 Scanning electron microscope (SEM) images of the FeNi-CAs bifunctional electrocatalysts prepared in Examples 1 (left) and 5 (right) of this invention;
[0031] Figure 3 The polarization curves of the FeNi-CAs bifunctional electrocatalyst prepared in Example 1 of this invention and commercial Pt / C+RuO2 are shown.
[0032] Figure 4 The cyclic voltammetric curves are those of the FeNi-CAs bifunctional electrocatalyst prepared in Example 1 of this invention and commercial Pt / C+RuO2. Detailed Implementation
[0033] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0035] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0036] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0037] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0038] like Figure 1 The present invention provides a method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, comprising the following steps:
[0039] S1: Add soluble nickel salt to chitosan solution, stir to completely dissolve soluble nickel salt, then add nanocellulose suspension, and continue stirring to mix evenly;
[0040] The soluble nickel salt is at least one of nickel chloride, nickel nitrate, and nickel sulfate.
[0041] The chitosan solution is prepared by adding chitosan to an acidic solution and stirring until the chitosan is completely dissolved. The acidic solution is any one of acetic acid, hydrochloric acid, nitric acid, and sulfuric acid.
[0042] The specific process in this step is as follows: 0.5-2g of chitosan is added to 10-100mL of an acidic solution with a mass fraction of 2-10wt%, and stirred for 2-10h to completely dissolve the chitosan and obtain a chitosan solution; then 10mL of a solution containing 0.1-0.5g of nickel chloride is added to the above chitosan solution, and stirred to completely dissolve the nickel chloride; finally, 10-100mL of a nanocellulose suspension with a mass fraction of 1%-5% is added, and stirred vigorously for 1-5h to make the system uniformly dispersed.
[0043] S2: The mixture obtained in step S1 is freeze-dried to obtain nickel-doped chitosan aerogel, and the nickel-doped chitosan aerogel is carbonized once to obtain nickel-doped carbon aerogel.
[0044] Specifically, before freeze-drying, the mixture obtained in step S1 is placed in an ultra-low temperature freezer overnight, causing the mixture to freeze and transform into a solid.
[0045] In addition, the temperature of the carbonization process is 700-900℃ and the time is 2-5 hours.
[0046] S3: The nickel-doped carbon aerogel is placed in a phthalocyanine iron solution and stirred to obtain a nickel-doped carbon aerogel adsorbed with phthalocyanine iron. Then, the nickel-doped carbon aerogel adsorbed with phthalocyanine iron is placed in a mixed atmosphere of Ar and H2 for secondary carbonization treatment to obtain the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst.
[0047] 2. Specifically, nickel-doped carbon aerogel is placed in 50 mL of a solution containing 1–100 mg of phthalocyanine iron for 1–5 h, then filtered and dried to obtain nickel-doped carbon aerogel adsorbed with phthalocyanine iron. The nickel-doped carbon aerogel adsorbed with phthalocyanine iron is then placed in a tube furnace at 500–800 °C and carbonized under an Ar / H2 atmosphere (a mixed atmosphere of Ar and H2) for 2–5 h to obtain the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst. The phthalocyanine iron solution is prepared by adding phthalocyanine iron to an organic solvent and stirring until completely dissolved, wherein the organic solvent is at least one selected from methanol, ethanol, acetone, and N,N-dimethylformamide.
[0048] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0049] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0050] Example 1
[0051] A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst includes the following steps:
[0052] a. Weigh 1g of chitosan using an electronic balance, add it to 50mL of 2wt% acetic acid solution, and stir mechanically for 2h; then add 10mL of a solution containing 0.1g of nickel chloride to a beaker containing the chitosan solution and stir evenly; finally, add 50mL of 1% nanocellulose suspension and stir vigorously for 5h.
[0053] b. Place the above mixture in an ultra-low temperature freezer overnight and freeze-dry it; then carbonize the freeze-dried aerogel in a tube furnace at 900°C for 2 hours.
[0054] c. The carbon aerogel material after one carbonization is placed in 50 mL of N,N-dimethylformamide solution containing 25 mg phthalocyanine iron for 5 h, filtered and dried; then it is placed in a tube furnace at 500 °C and carbonized for 2 h under an Ar / H2 atmosphere.
[0055] Example 2
[0056] A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst includes the following steps:
[0057] a. Weigh 0.5g of chitosan using an electronic balance, add it to 10mL of 5wt% acetic acid solution, and stir mechanically for 5h; then add 10mL of a solution containing 0.5g of nickel chloride to a beaker containing the chitosan solution and stir evenly; finally, add 100mL of 5% nanocellulose suspension and stir vigorously for 5h.
[0058] b. Place the above mixture in an ultra-low temperature freezer overnight and freeze-dry it; then carbonize the freeze-dried aerogel in a tube furnace at 700°C for 5 hours.
[0059] c. Place the carbon aerogel material after one carbonization in 50 mL of N,N-dimethylformamide solution containing 1 mg of phthalocyanine iron for 5 h, filter, and dry; then place it in a tube furnace at 800 °C and carbonize it under an Ar / H2 atmosphere for 5 h.
[0060] Example 3
[0061] A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst includes the following steps:
[0062] a. Weigh 2g of chitosan using an electronic balance, add it to 50mL of 2wt% acetic acid solution, and stir mechanically for 5h; then add 10mL of a solution containing 0.2g of nickel chloride to a beaker containing the chitosan solution and stir evenly; finally, add 70mL of 1% nanocellulose suspension and stir vigorously for 5h.
[0063] b. Place the above mixture in an ultra-low temperature freezer overnight and freeze-dry it; then carbonize the freeze-dried aerogel in a tube furnace at 800°C for 5 hours.
[0064] c. Place the carbon aerogel material after one carbonization in 50 mL of N,N-dimethylformamide solution containing 100 mg phthalocyanine iron for 5 h, filter and dry; then place it in a tube furnace at 600 °C and carbonize it under an Ar / H2 atmosphere for 5 h.
[0065] Example 4
[0066] A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst includes the following steps:
[0067] a. Weigh 1g of chitosan using an electronic balance, add it to 50mL of 2wt% acetic acid solution, and stir mechanically for 5h; then add 10mL of a solution containing 0.1g of nickel chloride to a beaker containing the chitosan solution and stir evenly; finally, add 50mL of 1% nanocellulose suspension and stir vigorously for 5h.
[0068] b. Place the above mixture in an ultra-low temperature freezer overnight and freeze-dry it; then carbonize the freeze-dried aerogel in a tube furnace at 700°C for 2 hours.
[0069] c. The carbon aerogel material after one carbonization is placed in 50 mL of N,N-dimethylformamide solution containing 25 mg phthalocyanine iron for 5 h, filtered and dried; then it is placed in a tube furnace at 800 °C and carbonized for 5 h under an Ar / H2 atmosphere.
[0070] Example 5
[0071] A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst includes the following steps:
[0072] a. Weigh 2g of chitosan using an electronic balance, add it to 100mL of 2wt% acetic acid solution, and stir mechanically for 5h; then add 10mL of a solution containing 0.1g of nickel chloride to a beaker containing the chitosan solution and stir evenly; finally, add 50mL of 1% nanocellulose suspension and stir vigorously for 5h.
[0073] b. Place the above mixture in an ultra-low temperature freezer overnight and freeze-dry it; then carbonize the freeze-dried aerogel in a tube furnace at 900°C for 2 hours.
[0074] c. Place the carbon aerogel material after one carbonization in 50 mL of N,N-dimethylformamide solution containing 25 mg phthalocyanine iron for 5 h, filter and dry; then place it in a tube furnace at 600 °C and carbonize it under an Ar / H2 atmosphere for 2 h.
[0075] Figure 2 These are scanning electron microscope (SEM) images of the FeNi-CAs bifunctional electrocatalysts prepared in Examples 1 and 5. Figure 2 It can be seen that the surface of this carbon aerogel has a rich pore structure, thus possessing more catalytically active sites.
[0076] Figure 3 The polarization curves of the FeNi-CAs bifunctional electrocatalyst prepared in Example 1 and commercial Pt / C+RuO2 are shown to evaluate their OER electrocatalytic performance in 1 mol / L KOH solution. Figure 3 It can be observed that the commercially available Pt / C+RuO2 has a relatively small overpotential of 300 mV. In addition, this FeNi-CAs carbon aerogel catalyst also shows good OER catalytic potential (η10 = 370 mV).
[0077] Figure 4 Cyclic voltammetry curves of the FeNi-CAs bifunctional electrocatalyst prepared in Example 1 and commercial Pt / C+RuO2 are shown to evaluate their ORR performance in an oxygen-filled 0.1 mol / L KOH solution. Figure 4 It can be seen that all catalysts exhibit characteristic cathode peaks, indicating a significant oxygen reduction process; and FeNi-CAs carbon aerogels exhibit excellent ORR activity, with their maximum reduction peak (0.89V) being superior to that of commercial Pt / C+RuO2 electrodes (0.85V).
[0078] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, characterized in that, Includes the following steps: S1: Add soluble nickel salt to chitosan solution, stir to completely dissolve soluble nickel salt, then add nanocellulose suspension, and continue stirring to mix evenly; S2: The mixture obtained in step S1 is freeze-dried to obtain nickel-doped chitosan aerogel, and the nickel-doped chitosan aerogel is carbonized once to obtain nickel-doped carbon aerogel. S3: The nickel-doped carbon aerogel is placed in a phthalocyanine iron solution and stirred to obtain a nickel-doped carbon aerogel adsorbed with phthalocyanine iron. Then, the nickel-doped carbon aerogel adsorbed with phthalocyanine iron is placed in a mixed atmosphere of Ar and H2 for secondary carbonization treatment to obtain the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst.
2. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, In step S1, the mass ratio of chitosan to nickel chloride is (0.5-2)g:(0.1-0.5)g.
3. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, In step S1, the soluble nickel salt is at least one of nickel chloride, nickel nitrate, and nickel sulfate.
4. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, The chitosan solution is prepared by adding chitosan to an acidic solution and stirring until the chitosan is completely dissolved. The acidic solution is any one of acetic acid, hydrochloric acid, nitric acid, and sulfuric acid.
5. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, In step S2, the temperature of the carbonization process is 700–900℃ and the time is 2–5 hours.
6. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, In step S3, the nickel-doped carbon aerogel is placed in an iron phthalocyanine solution for 1 to 5 hours.
7. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, In step S3, the temperature of the secondary carbonization treatment is 500–800℃, and the time is 2–5 hours.
8. The method for preparing a transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst according to claim 1, characterized in that, The iron phthalocyanine solution contains iron phthalocyanine at a concentration of (1-100) mg / 50 mL.
9. A transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst, characterized in that, It is prepared by the method described in any one of claims 1 to 8.
10. The application of the transition metal-doped chitosan-based carbon aerogel bifunctional electrocatalyst as described in claim 9 in the field of zinc-air batteries.
Citation Information
Patent Citations
Carbon aerogel supported cobalt monatomic catalyst for metal-air battery, and preparation method and application thereof
CN113363514A
Preparation method of carbon / nickel oxide composite electrode material
CN113436905A